Vibriosis Vaccine Development: Pathogenesis, Immunological And Molecular Characterization Of Vibrio Alginolyticus - Mohd Taib, Nor Azizah (2000)
The aim of the research is to develop an effective vaccine against vibriosis. Vibriosis is a bacterial disease caused by Vibrio spp due to the intensive production activity of brackishwater ponds and cage-cultured fish. The pathogenicity study of V alginolyticus was performed by challenging the juvenile seabass (10±0.75 g) with 5 different isolates of V alginolyticus at different cell concentrations. All the isolates caused mortality to fish at a concentration as low as 0.2 optical density (6.28 X 103 CFU/ml). Ultrastructure changes observed by scanning and transmission electron microscopy, revealed the presence of V .alginolyticus in the gills, liver, muscle, spleen and kidney of infected fish. In addition, the V .alginolyticus cells were observed in the spleen. These pathological changes showed that V alginolyticus was responsible for the death of the infected seabass.